Resource management a correlate of studetns' achievement in secondary school physics in Oyo state (2011)
This paper focused on resources management as a predictor of studetns' achievement in secondary school physics. Resources management is measured using some six vriables as related to physics. These include planning of physics class; replacement of damaged physics facilities; maintenance of physics facilities; frequency of repairs of physics facilities; organization of the use of physics facilities; and marking exericise of studetns' assignments by the physics teacher. A total of 1,029 SS1 physics students from 40 schools with their principals participated in the study. Descriptive statistics and multiple regression analysis were used to answer the two reseach questions. Two research instruments-Physics Achievement Test (PAT) and the School Questionnaire (SQ) were used in this study. The results of the study show that the level of resoruces management can be avaerage. Again four out of six independent variables contribute significantly to the prediction of students' achievement is physics. It is therefore recommended that teachers should organize their classes as scheduled and that repairs should be done regularly on malfunctioning physics facilities.